If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2y + 3) + -6 + -4(2y + 3) = -3y Reorder the terms: 6(3 + 2y) + -6 + -4(2y + 3) = -3y (3 * 6 + 2y * 6) + -6 + -4(2y + 3) = -3y (18 + 12y) + -6 + -4(2y + 3) = -3y Reorder the terms: 18 + 12y + -6 + -4(3 + 2y) = -3y 18 + 12y + -6 + (3 * -4 + 2y * -4) = -3y 18 + 12y + -6 + (-12 + -8y) = -3y Reorder the terms: 18 + -6 + -12 + 12y + -8y = -3y Combine like terms: 18 + -6 = 12 12 + -12 + 12y + -8y = -3y Combine like terms: 12 + -12 = 0 0 + 12y + -8y = -3y 12y + -8y = -3y Combine like terms: 12y + -8y = 4y 4y = -3y Solving 4y = -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 4y + 3y = -3y + 3y Combine like terms: 4y + 3y = 7y 7y = -3y + 3y Combine like terms: -3y + 3y = 0 7y = 0 Divide each side by '7'. y = 0 Simplifying y = 0
| 8(x+3)=7x+12 | | 10-w=-14 | | 7x-3+2x=9-3x | | 9+2x+9=225 | | -5x^2+15x+50=0 | | x^2+8xy-9y^2=0 | | -4y-13=6y+7 | | 5b-6=3+8b+72 | | 4v+2v=30 | | 3(7z-1)-5(3+z)=-14 | | x+.12x=34.72 | | -3(2t-1)=-3 | | 5n+3=2 | | -5(b-4)-7=13-5b | | x+(2x-4)+(x+4)=180 | | x^2+8xy-9x^2=0 | | 9s-5g=-4u | | 8x+10=4x+36 | | -6t-[4-(2-3t)]=4(t+1) | | 10-j=3j+66 | | 17-20q=(-13-5a)4 | | 5x+2-3=-3x+10x | | 26-z=19 | | -3.1=4.1 | | 6x+11=5x+3 | | 4(r+3)=3(r-5)+9 | | (3+y)y= | | 20-8x=44 | | -33=2+5x | | 9=6+(x+2) | | D+23=35 | | 7x+17+3x-20=90 |